2021
DOI: 10.1126/sciadv.abd8750
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of digital contact tracing: Role of age, transmission setting, adoption, and case detection

Abstract: The efficacy of digital contact tracing against COVID-19 epidemic is debated: smartphone penetration is limited in many countries, non-uniform across age groups, with low coverage among elderly, the most vulnerable to SARS-CoV-2. We developed an agent-based model to precise the impact of digital contact tracing and household isolation on COVID-19 transmission. The model, calibrated on French population, integrates demographic, contact-survey and epidemiological information to describe the risk factors for expo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…We have then simulated contact tracing, both manual (MCT) and digital (DCT), and shown that both can yield a strong decrease in the final epidemic size. The relative impact of contact tracing is actually larger for lower reproduction numbers, and its cost lower: lower R 0 means indeed a slower epidemic reaching fewer individuals even without interventions, so that contact tracing needs to be applied to fewer cases, and fewer people need to be quarantined to mitigate the epidemic (this is in agreement with the results of [30]). Contact tracing thus becomes more efficient in a situation where the epidemic is already partially mitigated by other measures that keep R 0 as low as possible, showing the importance of combining contact tracing with other measures such as masks or hand hygiene, and that contact tracing might lose efficiency at too large R 0 .…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…We have then simulated contact tracing, both manual (MCT) and digital (DCT), and shown that both can yield a strong decrease in the final epidemic size. The relative impact of contact tracing is actually larger for lower reproduction numbers, and its cost lower: lower R 0 means indeed a slower epidemic reaching fewer individuals even without interventions, so that contact tracing needs to be applied to fewer cases, and fewer people need to be quarantined to mitigate the epidemic (this is in agreement with the results of [30]). Contact tracing thus becomes more efficient in a situation where the epidemic is already partially mitigated by other measures that keep R 0 as low as possible, showing the importance of combining contact tracing with other measures such as masks or hand hygiene, and that contact tracing might lose efficiency at too large R 0 .…”
Section: Discussionsupporting
confidence: 72%
“…As traditional MCT is labour intensive and limited by people's ability to correctly remember contacts, app-based DCT is seen as a potentially useful complement and has been deployed in several countries [18,21,47]. Its actual efficiency, however, has been debated, in particular with respect to the level of adoption needed for it to make a difference [18,29,30,47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have examined the effectiveness and limitations of TTIS on transmission of SARS-CoV-2 and other pathogens [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Many studies have shown that TTIS can substantially reduce the pathogen reproductive number, R t , but its efficacy depends on the importance of pre-symptomatic and asymptomatic transmission, delays between symptom onset and being tested, and the fraction of infections that are tested and traced [14,19,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…The success of such large-scale digital mitigation strategies mostly depends, for a voluntary and decentralized approach, on acceptance in the general population, proper usage of the application, and technical properties [13]. Numerous studies have already been conducted regarding benefits and limitations of DigCT concerning its use during the COVID-19 pandemic [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. It was found that strong mitigation effects could only be observed with high app participation.…”
Section: Introductionmentioning
confidence: 99%